THE ROLE OF SOFT SKILLS FOR PERSONAL AND PROFESSIONAL DEVELOPMENT - Makhmetova Darina; Mehmet Akif Sözer (European Research Materials, 2023)
The modern world is in a global flow of information and as a consequence the demands on human capital are changing rapidly. Socio-economic trends affect the personal development trajectories of each individual. Consequently, professional fields are undergoing transformation and the requirements for professionals are being modernised. Nowadays, it is not enough to have only academic knowledge in a certain professional field, as information becomes outdated and needs to be updated regularly. The highest priority is skills. These skills can be either vocational or personal skills, which are supra-curricular and do not relate to a specific field of work. In fact, it is the soft skills that are most in demand in today’s world. Soft skills are a broad range of skills such as organisational skills, communication skills, creativity, adaptability, learning ability, emotional intelligence, etc. Soft skills are a set of generic skills that are stable in constantly changing circumstances. These skills are called the skills of the future and as predicted by experts in the economic field, this type of skills will be independent of economic changes and technological advances, and will affect all areas of society.